2020
DOI: 10.48550/arxiv.2011.06072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A high-order / low-order (HOLO) algorithm for preserving conservation in time-dependent low-rank transport calculations

Zhuogang Peng,
Ryan G. McClarren

Abstract: Dynamical low-rank (DLR) approximation methods have previously been developed for time-dependent radiation transport problems. One crucial drawback of DLR is that it does not conserve important quantities of the calculation, which limits the applicability of the method. Here we address this conservation issue by solving a low-order equation with closure terms computed via a high-order solution calculated with DLR. We observe that the high-order solution well approximates the closure term, and the low-order sol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…First, we repeat here the low temperature, constant opacity hohlraum problem presented in Brunner [2], (and with a slight modifications later, in [12,23]). This problem was the first benchmark that was offered of its hohlraum type.…”
Section: Brunner Xy Hohlraum 2002mentioning
confidence: 94%
“…First, we repeat here the low temperature, constant opacity hohlraum problem presented in Brunner [2], (and with a slight modifications later, in [12,23]). This problem was the first benchmark that was offered of its hohlraum type.…”
Section: Brunner Xy Hohlraum 2002mentioning
confidence: 94%
“…The reference solution to this problem is given by the standard de facto Ganapol's benchmark test [10] and this problem has been investigated for dynamical low-rank approximations in [25,24]. As time increases, the scalar flux Φ(t, x) = 1 −1 f (t, x, µ) dµ moves to the left and right side of the spatial domain, showing a discontinuous (or shock) profile at the front.…”
Section: Radiation Transport Equationmentioning
confidence: 99%
“…Common methods require high computational costs or parameter tuning to yield a satisfactory approximation. Uses of dynamical low-rank approximation for this benchmark are [37,36,8], where it is observed that high ranks are needed to achieve a desired level of accuracy. Nevertheless, in comparison to classical methods, DLRA yields reduced runtimes and memory requirements.…”
Section: Line Source Benchmarkmentioning
confidence: 99%
“…More exact dose calculation can be achieved by an appropriate Monte Carlo (MC) algorithm, where individual interacting particles are directly simulated [4]. However, while recent performance-tuned MC The efficiency of dynamical low-rank approximation has been demonstrated in several applications, including kinetic theory [14,15,37,36,16,12,13,8,30,11]. Two main challenges of DLRA in the context of kinetic theory and radiation transport specifically are the preservation of mass as well as capturing the asymptotic limit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation